Five year long term results of total joint arthroplasties in the treatment of trapeziometacarpal osteoarthritis - Gómez-Garrido, David; Triviño-Mayoral, Victor; Delgado-Alcala, Victor; Cervera-Irimia, Javier; Medina-Lorca, Maria; Sánchez-Sánchez, Felix; Ibáñez-Vicente, Cristina; Pérez-Gurbindo, Ignacio; Meccariello, Luigi; Rollo, Giuseppe; Pica, Giuseppe; Tomarchio, Alessandro; et al. (Acta Biomedica Atenei Parmensis, 2019)
Introduction: Trapeziometacarpal (TMC) osteoarthritis is a common disease. Patients with advanced disease who have failed conservative treatment have different surgical options, including total joint prosthesis. The aim of this study was to investigate the long-term outcome and complications of trapeziometacarpal (TMC) total arthroplasty. Materials and Methods: One hundred and forty-seven patients with TMC osteoarthritis were surgically treated with TMC arthroplasty, and one hundred and thirty-seven patients were seen for follow-up (102 women and 35 men). At follow -up patients were asked to complete a visual linearanalogue scale (VAS) for satisfaction with the result of the operation and persisting pain from the thumb, the Spanish validated Disabilities of the Arm, Shoulder and Hand (DASH) questionnaire was used to evaluate function of the affected hand.(9) The radiological examination consisted of posterior-anterior and oblique radiographs. In preoperative radiographs Eaton-Little was used, and in postoperative radiographs were assessed with regard to implant loosening and alignment. Results: The subjective outcome was satisfactory in 126 cases (92 %), 14 (12 %) patients would undergo the same procedure in the other hand. The DASH questionnaireswere 19.55 (range 5.6-33,5) on average, and EVA was 1 on average. The mean key pinch strength was 5.8 Kg at 5 years follow-up. The most frequent postoperative complication was De Quervain tenosynovitis (21%), other complications were: Cup loosening (3.6%), traumatic dislocation (3,6%). The prosthesis was removed in nine cases (7%). There were four intraoperative complications. The survival rate for ARPE prosthesis was 92,7% at 60,5 months. TMC total arthroplasty offers a reliable treatment alternative in patients with thumb carpometacarpal joint osteoarthrosis which conservatives’ treatment had failed. Conclusions: The TMC joint prosthesis is an option for patients with TCM osteoarthritis, provides satisfactory outcomes and has a low failure rate.(www.actabiomedica.it)